GAMBARAN GRIT PADA MAHASISWA YANG MEMILIKI ONLINE SHOP - Albertus Suhardinata Dharmawan (Universitas Katolik Widya Mandala Surabaya, 2022)
ABSTRACT Technological advances make everything fast so, there are many changes in various sectors including the industrial sector. The process of buying and selling transactions can now be done digitally and online. This progress is used by college students to get income to meet their needs. The problem that arises when students have an online shop is how the lecture process and the business online shop run optimally? Grit is a combination of consistency with passion, namely consistency with goals that have been set for a long period of time, and perseverance which means the ability to overcome the desire to give up (Duckworth, 2016). Grit is one of the differences so that online shops and lectures can run together and optimally. Researchers conducted research to determine the description of grit in college students who have an online shop. This research used a qualitative approach with a phenomenological type. The data obtained were analyzed using themethod led theory, especially deductive analysis. The research informants were undergraduate students with a minimum GPA of 2.75 and theage was online shop over 1 year. The results of the study found that the grit of the two informants was the same as the existing theory. There are 4 aspects, namely 1) interest, 2) practice, 3) purpose, and 4) hope that there are also factors that influence the growth of grit, namely 1) parenting, 2) culture and 3) experience. However, researchers found another factor, which is the situation where informants were forced to be independent because students had to migrate away from their parents. Keywords : Grit, Online Shop, Perseverence